Deaminative defluoroalkylation of α-trifluoromethylalkenes enabled by photoredox catalysis. Issue 2 (13th December 2022) - Zhang, Guodong; Wang, Lei; Cui, Liping; Gao, Pan; Chen, Feng
Abstract : A new photoredox-catalysed strategy to construct  gem -difluoroallylarenes from α-trifluoromethylalkenes and primary amines has been developed. This deaminative defluoroallylation is compatible with sterically hindered α-3° and 2° primary amines. Abstract : Herein, we disclose a new photoredox-catalysed strategy to access gem -difluoroallylarenes from α-trifluoromethylalkenes with sterically hindered primary amines via C–N and C–F bond activation. This deaminative and defluorinative allylation is generally compatible with diverse functional groups and sterically hindered α-3° and 2° primary amines.